Meningkatkan Kesadaran Prenatal Melalui Afirmasi Diri dan Yoga: Pendekatan Studi Kasus - Yustina Tyas Kurniawati (Jurnal Ilmiah Kebidanan (The Journal Of Midwifery), 2025)
Anchored in SDGâ€¯3â€™s imperative to â€œensure healthy lives,â€ but roughly 20% of women experience anxiety worldwide, including pregnant women. To overcome it, they should deepen self-knowledge, bolster self-compassion, and enhance resilience against prenatal distress. This study uses a one-group post-test only design with purposive sampling to assess the impact of combined selfâ€‘affirmation and prenatal yoga on mindfulness. Employing a pre-experimental, singleâ€‘case design with healthy women at 20â€“36â€¯weeksâ€™ gestation, the intervention was practiced by a midwife who is certified yoga facilitator. After each weekly private yoga session, including breathing exercises, verbal self-affirmation, yoga sequences, and praying, participants completed the FFMQ to assess mindfulness. Among 18 pregnant women, most were primiparous. Based on the FFMQ results, mean scores for Observing (30.3), Describing (24.1), and Acting with Awareness (19.2) were above the median values 29.5, 24, 19.5, while mean Nonâ€‘Judging (19.0) closely approximated its median (19.5), and mean Nonâ€‘Reactivity (20.6), while the median (20.0). The combined prenatal yoga and selfâ€‘affirmation program improved key mindfulness facets: Observing, Describing, and Acting with Awareness, while preserving Nonâ€‘Judging and Nonâ€‘Reactivity, thereby enhancing attentional focus and emotional labeling to buffer prenatal stress. Good scores mean greater mindfulness. This approach effectively fosters emotional resilience and wellâ€‘being in pregnancy.